Adrenal Myelolipoma- A Rare Case Report - Vijayalaxmi V. Suranagi; Prakash R.Malur; Hema B.Bannur; Reshma Davanageri; R.B. Nerli (Al Ameen Medical College, 2009)
Adrenal myelolipoma (AML) is a rare benign tumour composed of mature adipose tissue and hematopoietic tissue. Very few cases have been reported. Most of these patients are asymptomatic. We present a rare case of Adrenal Myelolipoma where the patient presented with hypertension and a clinical suspicion of Pheochromocytoma, which turned out to be an Adrenal myelolipoma. Adrenal myelolipoma is a rare entity, not encountered frequently and can occur as an incidental finding. Awareness regarding this entity is very much essential to exclude surgical exploration or extensive surgery.